Martha Stewart's cake perfection : 100+ recipes for the sweet classic, from simple to stunning - Weibull, Lennart (Photographer); Stewart, Martha (Clarkson Potter/Publishers, 2020)
Martha Stewart perfects the art of cakes with 125 recipes for all occasions, featuring exciting flavors, must-try designs, and dependable techniques. Martha Stewart's authoritative baking guide presents a beautiful collection of sheet cakes and chiffons, batters and buttercreams, and tiers and tortes to tackle every cake creation. Teaching and inspiring like only she can, Martha Stewart demystifies even the most extraordinary creations with her guidance and tricks for delicious cake perfection. From everyday favorites to stunning showstoppers, Martha creates bold, modern flavors and striking decorations perfect for birthdays, celebrations, and big bakes for a crowd. Think comforting classics like Snickerdoodle Crumb Cake and Chocolate Angel Food Cake and treats that take it up a notch like Ombre Strawberry Cake and Marble Souffle, plus a whole chapter on cupcakes alone. With Martha's expert tips, even the most impressive, towering cakes will be in your reach.